Calibration of the Water Balance Model for the Upper Cimanuk Catchment Area for Raw Water Supply - Permana, Sulwan; Susetyaningsih, Adi (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
The main task of PDAM Tirta Intan Garut Regency is to manage raw water into clean water for customers. The management of raw water supply in Bayongbong District for the community still relies on springs with a gravity system, deep well pumps and rivers. The flow of the Cimanuk River in Bayongbong District can be used to provide raw water. Four rainfall stations are used. Average rainfall is calculated using the Thiessen method. The raw water collection point does not have a automatic water level recorder (AWLR), so it is necessary to create a model to obtain the discharge at the collection point. The model used is the water balance model from F.J. Mock. Calibration of model parameters was carried out on observed discharge at Cimanuk-Bayongbong AWLR and Cimanuk-Bojongloa AWLR. To test the reliability of the model, NSE and RMSE values ​​were used. The NSE and RMSE values ​​in the Cimanuk-Bayongbong catchment area are 0.515 and 3.615 and Cimanuk-Bojongloa are 0.593 and 4.813. The results of the model parameter calibration are used to calculate the discharge at the collection point. The calibration result ​​at the collection site are exposed surface 50%, infiltration coefficient 0.5: recession coefficient 0.35: catchment area characteristic factor 10%; and soil moisture capacity 200 mm. The dependable flow is calculated based on Q90% probability, water availability in July, August, September and October is 0.078 m3/s; 0.025 m3/s; 0.035 m3/s; and 0.025 m3/s. Water availability in that month is smaller than the discharge requirement for the next five and ten years, namely ranging from 0.134 m3/s to 0.168 m3/s and 0.145 m3/s to 0,182 m3/s.